2009
DOI: 10.1071/wf08009
|View full text |Cite
|
Sign up to set email alerts
|

Improving estimates of savanna burning emissions for greenhouse accounting in northern Australia: limitations, challenges, applications

Abstract: Although biomass burning of savannas is recognised as a major global source of greenhouse gas emissions, quantification remains problematic with resulting regional emissions estimates often differing markedly. Here we undertake a critical assessment of Australia’s National Greenhouse Gas Inventory (NGGI) savanna burning emissions methodology. We describe the methodology developed for, and results and associated uncertainties derived from, a landscape-scale emissions abatement project in fire-prone western Arnh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
160
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 168 publications
(164 citation statements)
references
References 65 publications
4
160
0
Order By: Relevance
“…An essential premise underlying Australia's recently developed savanna burning methodology (Russell-Smith et al 2009a;DCCEE 2012;Meyer et al 2012) is that reductions in fire frequency result in reduced GHG emissions because more of the fuel biomass (mostly grass and leaf litter) is decomposed biologically through pathways that, compared with savanna fires, produce lower relevant emissions per unit biomass consumed (Cook and Meyer 2009). In unburnt north Australian savannas, emissions of CH 4 and N 2 O arising from biological decomposition pathways are likely to be less than 10 % than that from fire (Cook and Meyer 2009;Jamali et al 2011).…”
Section: National Accounting and Project-scale Savanna Burningmentioning
confidence: 99%
“…An essential premise underlying Australia's recently developed savanna burning methodology (Russell-Smith et al 2009a;DCCEE 2012;Meyer et al 2012) is that reductions in fire frequency result in reduced GHG emissions because more of the fuel biomass (mostly grass and leaf litter) is decomposed biologically through pathways that, compared with savanna fires, produce lower relevant emissions per unit biomass consumed (Cook and Meyer 2009). In unburnt north Australian savannas, emissions of CH 4 and N 2 O arising from biological decomposition pathways are likely to be less than 10 % than that from fire (Cook and Meyer 2009;Jamali et al 2011).…”
Section: National Accounting and Project-scale Savanna Burningmentioning
confidence: 99%
“…This program, modelled on and continuing indigenous patchwork burning patterns, was funded by carbon offset payments from large energy companies. Building on extensive trials, research consistently confirmed and quantified the value of early-season burns compared with late-season fires, with benefits including reduced CO 2 emissions, conservation of biodiversity and cultural practices, and connections to country and improvements in health and education in remote communities (Russell-Smith et al 2009). The cooperative program covered the great bulk of the savannas and involved indigenous communities, conservation NGOs, graziers, and government agencies.…”
Section: Scaled-up Savannas Burningmentioning
confidence: 99%
“…These dynamics are currently being investigated (Douglass et al 2011). Payments for enhanced carbon sequestration and cultural and biodiversity conservation through changing burning practices are already under way (Russell-Smith et al 2009). Furthermore, these practices are likely to expand, as the Commonwealth's Carbon Farming Initiative lists savanna burning as eligible for government's carbon grants (DCCEE, www.climatechange.gov.au/government/initiatives/ carbon-farming-initiative/activities-eligible-excluded/additionalactivities-positive-list/positive-list-guidelines-proposal-form.aspx).…”
Section: Carbon Marketsmentioning
confidence: 99%
See 1 more Smart Citation
“…Paradoxically, imposing anthropogenic disturbance regimes, such as strategic grazing, within conservation reserves may help suppress high impact environmental alien grasses (Popay and Field 1996;Friedel et al 2011). Prescriptions for optimal fire regimes continue to be refined in different parts of Australia in response to competing land uses (Russell-Smith et al 2009;Friedel et al 2014) and major ongoing changes in water management and flow regimes are expected in Australia's largest catchment, the Murray-Darling Basin (Pittock and Connell 2010) and elsewhere. However, implications for grass invasions need to be better integrated into land management recommendations and prescriptions.…”
Section: Disturbance Regimesmentioning
confidence: 99%